PENGEMBANGAN METODE BARU PENENTUAN CHEMICAL OXYGEN DEMAND (COD) BERBASIS SEL FOTOELEKTROKIMIA: KARAKTERISASI ELEKTRODA KERJA LAPIS TIPIS TiO2/ITO - Nurdin, M.; Wibowo, W; B., M.; Surahman, H; Krisnandi, Y K; Gunlazuardi, J (Makara Journal of Science, 2009)
Development of A Novel Methode for COD (Chemical Oxygen Demand) Measurement based on Photoelectrochemical Cell: Characterization of TiO2/ITO Film Working Electrode. Nanosize TiO2 film, immobilized on an ITO (Indium Tin Oxide) glass, was successfully fabricated. The film was prepared by a dip coating technique in a hydrothermal sol-gel system and subjected to a heat treatment at 100° C up to 450° C. Characterization of the film by XRD, AFM, BET methods revealed the occurrence of anatase form and 9.64 nm in crystallite size; having three dimensional profile and roughness with height of typically 9.8 nm; and surface area of 58.21 m2 /g. The film then was employed as a working electrode in a photo electrochemical system (PES). This PES generated a photocurrent that proportional to the organic chemical concentration in the water sample. Integration of the photocurrent versus time gives a charge (Q) that represent the event of complete mineralization of organic chemical in the TiO2 surface and can be correlated to the Chemical Oxygen Demand (COD) of measured water. This system has a potential to be developed for a novel COD sensor